A reversed approach for simultaneous mandibular symphyseal split osteotomy and genioplasty. Issue 9 (September 2019) - Shen, S.; Jiang, T.; Shen, S.G.; Wang, X.
Abstract: Performing a mandibular symphyseal split and genioplasty simultaneously and accurately is a technical challenge for the surgeon. The aim of this study was to validate a reversed approach for simultaneous symphyseal split and genioplasty. A cutting guide and a repositioning guide were designed and printed three-dimensionally in titanium. The symphyseal split and genioplasty were performed successfully. The accuracy of the technique appears to be appropriate for clinical application.